2018
DOI: 10.3390/cryst8020103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure Analysis and Decomposition of RbAlH4

Abstract: RbAlH 4 , a member of the complex metal aluminum hydride family, can be synthesized phase pure by different synthesis routes. Synthesis from the metals by a mechanochemical reaction requires the presence of a catalyst, but also emphasizes the reversibility of hydrogenation. The structure refinement of neutron diffraction data confirms that RbAlD 4 is isostructural to KAlD 4. The decomposition proceeds via two distinct processes at temperatures above 275 • C. However, the structures formed during decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Melting processes together with the appearance of unsolved intermediate structures lead to the simple hydrides RbH and CsH [58] . TG-DSC measurements of RbAlH 4 showed that only 45% of the expected hydrogen release is achieved up to 650 K [38] .…”
Section: Decomposition Of α-Lialhmentioning
confidence: 96%
See 1 more Smart Citation
“…Melting processes together with the appearance of unsolved intermediate structures lead to the simple hydrides RbH and CsH [58] . TG-DSC measurements of RbAlH 4 showed that only 45% of the expected hydrogen release is achieved up to 650 K [38] .…”
Section: Decomposition Of α-Lialhmentioning
confidence: 96%
“…In the orthorhombic structure of RbAlD 4 (space group Pnma ) the Rb + cation is coordinated by ten deuterium atoms, coordination [10] , within a coordination distance between 2.818(6) and 3.332(3) Å ( Fig. 4 d) [38] . The deuterium atoms belong to 7 different [AlD 4 ] − deuteride anions.…”
Section: Alkali Metal Aluminum Tetradeuteridesmentioning
confidence: 99%
“…If this material follows the group 1 tendency regarding dehydrogenation reactions, RbAlH 4 could reach a 2.5 wt.% of reversible hydrogen storage. Weidenthaler et al reported the synthesis of RbAlH 4 from the metals Al, Rb, and with TiCl 3 as an additive; milling was performed in a hydrogen atmosphere (200 bar) [176]. Adkis et al reported the synthesis of RbAlH 4 by the reaction between LiAlH 4 and metallic Rb [177].…”
Section: The “Single Metal” Alanatesmentioning
confidence: 99%
“…This reaction yield was explained by the formation of a complex between the halide salts and the triethylaluminum, i.e., a Ziegler-type complex. RbAlH 4 , and the deuterated species were also produced by the metathesis reaction between NaAlH 4 , LiAlH 4 , or LiAlD 4 with RbCl or RbF promoted by ball milling [176]. RbAlH 4 or RbAlD 4 were further heated in an autoclave and then purified [176].…”
Section: The “Single Metal” Alanatesmentioning
confidence: 99%
See 1 more Smart Citation